2018
DOI: 10.1021/acsami.8b04718
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Macrophage Phenotype by Biodegradable Polyurethane Nanoparticles: Possible Relation between Macrophage Polarization and Immune Response of Nanoparticles

Abstract: Nanomaterials with surface functionalized by different chemical groups can either provoke or attenuate the immune responses of the nanomaterials, which is critical to their biomedical efficacies. In this study, we demonstrate that synthetic waterborne polyurethane nanoparticles (PU NPs) can inhibit the macrophage polarization toward the M1 phenotype but not M2 phenotype. The surface-functionalized PU NPs decrease the secretion levels of proinflammatory cytokines (TNF-α and IL-1β) for M1 macrophages. Specifical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
50
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 75 publications
(55 citation statements)
references
References 49 publications
4
50
1
Order By: Relevance
“…There was no significant difference in the M2/M1 ratio between CS‐PU cryogel and PU film. Both groups had an M2/M1 ratio of about 3, higher than that (about 0.5) reported for polylactide …”
Section: Resultscontrasting
confidence: 66%
See 1 more Smart Citation
“…There was no significant difference in the M2/M1 ratio between CS‐PU cryogel and PU film. Both groups had an M2/M1 ratio of about 3, higher than that (about 0.5) reported for polylactide …”
Section: Resultscontrasting
confidence: 66%
“…These data indicated that CS‐PU cryogel was superior to the conventional PLA in biocompatibility. Polyurethane nanoparticles and films were reported to inhibit the macrophage polarization toward the M1 phenotype . The good individual biocompatibility of PU and CS may explain the low immune reaction of the CS‐PU cryogel.…”
Section: Discussionmentioning
confidence: 99%
“…This repeated exposure of the implant to stress could be the start of a more, secondary, profibrotic process. The macrophage seems to be susceptible to modulation and has already been suggested as a target for a therapeutic approach to prevent capsular contraction [ 33 ]. Our results indicate only a slight increase in CD68 positivity in the outer layers of the Baker-IV capsules, and therefore, it is likely that one or more other types of immune cells, like different T-cell subsets, are also involved in this process [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Drug treatment is one of the most important approaches to achieve macrophage functionalization [ 3 ], and in addition to the widely used chemical drugs, nanomedicines are attractive due to their controlled drug release, prolonged half-life and lower side effects [ 4 ]. Indeed, nanoparticles have been used in therapeutic applications of anti-inflammation and macrophage-related disorders [ 5 ] and to inhibit tumor growth by inducing pro-inflammatory macrophage polarization [ 6 ]. In some cases, however, macrophages mutate into a pro-healing phenotype, resulting in tumor-associated macrophages (TAMs) that promote the metastasis, shifting tumors towards an immunosuppressive microenvironment, and thus increasing the resistance to cancer therapy [ 7 ].…”
Section: Introductionmentioning
confidence: 99%